MASLAHAH DAN BATASAN-BATASANNYA MENURUT AL-BÛTHÎ (Analisis Kitab Dlawâbith al-Mashlahah fi al-Syarî’ah al-Islâmiyyah) - Arfan, Abbas (De Jure: Jurnal Hukum dan Syari'ah, 2013)
Definition of al - mashlahah according to al - BÃ»thÃ® is : â€œ Something useful accoding to al - ShÃ¢ri â€˜ (Allah and His Messenger ) for the benefit of his servants , in keeping religion , life , intellect , lineage and their property , in accordance with the specific sequences contained in the maintenance category . â€œ Furthermore al - BÃ»thÃ® asserts that al - mashlahah can be used as a source of law if it meets the five criteria that he called al -mashlahah DlawÃ¢bith.Â  TheseÂ  fiveÂ  criteria Â areÂ  ;Â  (Â  a)Â  maslahahÂ  shouldÂ  be included in the scope of al - maqashid al - Syarâ€™iyyah the five , ( b ) maslahah does not contradict with the Qurâ€™an , ( c ) maslahah does not contradict with al - Sunnah , ( d ) maslahah does not contradict with al - Qiyas and ( e ) maslahah does not contradict with another benefit that is higher / stronger / more important . Thatâ€™s more or less the gist of the book DlawÃ¢bith mashlahah fi al - Shariâ€™ah al - Islamiyya , beside that in this paper , the authors tried to analyze critic al - BÃ»thÃ® against al - ThÃ»fÃ® on maslahah concept , in addition also critical analysis of the author to distribution and limitations of maslahah in al - BÃ»thÃ®â€™s version. DefinisiÂ  al-MashlahahÂ  menurutÂ  al-BÃ»thÃ®Â  adalah:Â  â€œSesuatuÂ  yangÂ  bermanfaat yang dimaksudkanÂ  olehÂ  al-Syariâ€™Â  (AllahÂ  danÂ  Rasul-Nya)Â  untukÂ  kepentingan hamba-Nya,Â  baikÂ  dalamÂ  menjagaÂ  agama,Â  jiwa,Â  akal,Â  keturunanÂ  danÂ  harta mereka,Â  sesuaiÂ  denganÂ  urutanÂ  tertentuÂ  yangÂ  terdapatÂ  diÂ  dalamÂ  kategori pemeliharaan tersebut.â€ Namun al-BÃ»thÃ® menegaskan bahwa al-Mashlahah dapat dijadikan sebagai sumber hukum jika memenuhi lima kriteria yang ia istilahkan dengan DlawÃ¢bithÂ  al-Mashlahah.Â  KelimaÂ  kriteriaÂ  tersebutÂ  adalah;Â Â  maslahah tersebut haruslah: (a) termasuk ke dalam cakupan al-MaqÃ¢shid al-Syarâ€™iyyah yang lima, (b) tidak bertentangan dengan al-Qurâ€™an, (c) tidak bertentangan dengan alSunnah, (d) tidak bertentangan dengan al-Qiyas dan (e) tidak bertentangan dengan kemaslahatanÂ  lainÂ  yangÂ  lebihÂ  tinggi/Â  lebihÂ  kuat/lebihÂ  penting.Â  Itulah lebih kurang intisariÂ  dariÂ  kitabÂ Â  DlawÃ¢bithÂ  al-Mashlahah fiÂ  SyarÃ®â€™ahÂ  al-IslÃ¢miyyah,Â  namun dalam makalah ini, penulis berusaha menganalisis kritik al-BÃ»thÃ® terhadap konsep maslahah al-ThÃ»fÃ®, disamping analisis kritis penulis terhadap pembagian maslahah dan batasannya versi al-BÃ»thÃ®.